INVESTIGATION OF THE THERMAL PERFORMANCE OF A CROSS-FLOW WATER COOLING TOWER WITH DIFFERENT PACKINGS (Journal of Engineering, 2008)
The present research involves experimental and theoretical work to study the performance of three kinds of packing (PVC, corrugated and flat plate asbestos) in a crossflow water cooling tower under different atmospheric conditions and then comparing the performance of them with each other. The experimental work included the design, constructions and installation of a cross-flow cooling tower test rig suitable for measuring the individual coefficients (kGa) and (k'a). The experimental results were found by varying the inlet air flow rate and inlet water flow rate which are used as an input data to the computer program for finding the available performance coefficient (NTU) using the method of Webb with some modifications. Least square method was then used to correlate the experimental results of (NTU) in terms of water to air ratio (L/G).